Efektivitas Strategi True or False Dalam Meningkatkan Kemampuan Berpikir Kritis pada Pembelajaran IPS di SD - Sari, Suci permata; Aryaningrum, Kiki; Ayurachmawati, Puji (Institut Teknologi Pendidikan Indonesia, 2022)
This research aims to improve critical thinking skills using the True or False strategy in social studies learning in elementary school. The research method used by the researcher is quantitative. Sources of data used by researchers are observations, interviews, essay tests,and documentation. The research data analysis techniques used were normality test, homogeneity test, hypothesis testing, and N-gain test. The subjects used were 30 students from class VA and 30 students from class VB. The results of the research in the experimental class showed that the essay test could improve critical thinking seen from the posttest normality test in the form of Xcount 36.47 while for Xtable 42.557 which was marked normal, the hypothesis obtained was tcount 7.7 while for ttable 2.00172 which means H0 is rejected and Ha is accepted, the N-gain of the experimental class is 60.1 with a good category, the results of observations made by researchers are that students can receive lessons well using the True or False strategy. On the essay sheet in the control class using the lecture method and book media using vidcall, the results of the calculation of the posttest normality test in the form ofXcount 24.45, while for Xtable 42.557 which is marked normal, the N-gain of the experimental class is 46.9% including the low category. It can be concluded that the effectiveness of the True or False strategy can improve students' critical thinking in terms of the experimentalclass experiencing the effectiveness of using the True or False strategy and the control class not being effective because it uses the lecture method.